Production-sharing agreements : an economic analysis - Bindemann, K (Oxford Institute for Energy Studies, 1999)
Production-Sharing Agreements (PSAs) are among the most common types of contractual arrangements for petroleum exploration and development. Under a PSA the state as the owner of mineral resources engages a foreign oil company (FOC) as a contractor to provide technical and financial services for exploration and development operations. The state is traditionally represented by the government or one of its agencies such as the national oil company (NOC). The FOC acquires an entitlement to a stipulated share of the oil produced as a reward for the risk taken and services rendered. The state, however, remains the owner of the petroleum produced subject only to the contractor’s entitlement to its share of production. The government or its NOC usually has the option to participate in different aspects of the exploration and development process. In addition, PSAs frequently provide for the establishment of a joint committee where both parties are represented and which monitors the operations.